THE EFFECT OF GIVING INSULIN LEAF TEA ON LOWERING BLOOD SUGAR IN ELDERLY PEOPLE WITH DIABETES MELLITUS IN POPAYATO VILLAGE THESIS - Lasanuddin, Hamna Vonny; Paneo, Ibrahim; Ilham, Rosmin; Tuloli, Melis (Jambura Nursing Journal, 2025)
Diabetes mellitus is a disease characterized by hyperglycemia caused by insulin resistance. Diabetes mellitus therapy has pharmacological and non-pharmacological, one of the non-pharmacological therapies is Giving Insulin Leaf Tea The purpose of this research was to determine the effect of giving Insulin Leaf Tea on Lowering Blood Sugar in Elderly People with Diabetes Mellitus in Popayato Village. The design was to use Quasy Experimental one group pre and post test. The population was all elderly people with Diabetes Mellitus using purposive sampling techniques while the number of samples was 20 respondents. Data analysis used paired t-test because the data distribution was normal. The results showed changes in the blood sugar levels of respondents before and after being given insulin leaf tea in Popayato Village. which shows that the average blood sugar before being given insulin leaf tea in Popayato Village was 214.40. After being given an intervention in the form of insulin leaf tea, the average blood sugar of respondents decreased to 167.35 mg / dL. The conclusion is that there is an effect of giving insulin leaf tea. The purpose was to determine the effect of giving insulin leaf tea on reducing blood sugar in the elderly with diabetes mellitus in Popayato Village. using a paired t test with a value of p,000 (p 0.05),.